Liquidity, Monetary Policy and Unemployment: A New Monetarist Approach - Mei Dong; Sylvia Xiaolin Xiao (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2017)
We discover a consumption channel of monetary policy in a model with money and government bonds. When the central bank withdraws government bonds (short-term or long-term) through open market operations, it lowers re- turns on bonds. The lower return has a direct negative impact on consumption by households that hold bonds, and an indirect negative impact on consumption by households that hold money. As a result, fi rms earn less pro fits from production, which leads to higher unemployment. The existence of such a consumption channel can help us understand the eects of unconventional monetary policy.
Keywords: E24; E40; E50; 330; interest rate; monetary policy; consumption; unemployment